IMPLEMENTING COOPERATIVE LEARNING BASED ON COMIC MEDIA TO ENHANCE SCIENCE LEARNING OUTCOMES AT ELEMENTARY SCHOOLS - Suratmin Suratmin (JURNAL PAJAR (Pendidikan dan Pengajaran), 2021)
This research was motivated by the passivity of the fourth grade students at SD N Mrisen 1 and SD N Trengguli 3 during the learning process, which resulted in less optimal of the students‘ learning outcomes. Therefore, the researcher provided an alternative to learning by applying a cooperative learning model using comic-based learning media for fourth grade students at SD N Mrisen 1 and SD N Trengguli 3 as a comparison. This study aimed to analyze the effect of cooperative learning model with comic book media on the students‘ learning outcomes. This study was experimental research which was conducted through tests, observation, and documentation. Based on the results of data analysis, the students' average score increased from 48.80 to 79.04. The results of this study indicated that cooperative learning model with comic media provided an effect on the students‘ learning outcomes in science at grade IV elementary schools. Based on the research, teachers were advised to use cooperative learning models and comic-based media in order to improve students‘ science learning outcomes.